Experimentação no ensino de química e avaliação da aprendizagem: o enredo da prática docente em foco - SILVA, Thanielle Souza (2019)
Experimentation began to gain more space in science teaching from the twentieth century. Since then, it is part of the teaching practice, or, as is more common to say, the teacher's imagination, usually as a symbol of pedagogical excellence in the area. Today, the experimentation is in a situation of rehabilitation or critical revision, therefore, its problematization in the educational context is important. From this perspective, this research aimed to understand teachers' conceptions about the universe of experimentation in chemistry teaching from the perspective of learning assessment, from the experimental practices applied in disciplinary planning in a sample of public high schools in the city of São Luís/Maranhão. The methodological approach was based on the qualitative approach, based on two instruments for data collection, which were the questionnaire and semi-structured interview, which were treated by content analysis and organized by systemic network. The results showed that teachers present physical infrastructure as a major factor in the decision to implement experimental activities in chemistry classes. Content is a key point in the planning of experimental activities and these are inspired by the textbooks and / or materials available. The approach of experimental activities is guided by the demonstrative perspective and the context of the practice and its relationship with daily life are given by examples. The evaluation of the experimental activities happens similarly to the conventional classes and the evaluation instruments that teachers use the most are the tests, assignments and / or reports. Given this situation, it is evident the need to demystify the need for physical space to perform experimental activities, and broaden the look on them. We realized that investments in experimentation during initial teacher education can enable teachers to understand curriculum, assessment and methodologies in an integrated way, as we find ourselves at a time when students are attracted to many other interests outside the classroom. classroom. Therefore, teachers are challenged to review their pedagogical practices to suit the demands of a society that is constantly changing as well.